2017
DOI: 10.1248/bpb.b17-00481
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Retention and Anti-arthritic Effects in Collagen-Induced Arthritis Model Mice by Injectable Small Interfering RNA Containing Hydrogel

Abstract: Small interfering RNAs (siRNAs) are expected to offer a means of treating rheumatoid arthritis (RA) because they allow the specific silencing of genes related to RA pathogenesis. In our previous study, we reported that the siRNA targeted against RelA (anti-RelA siRNA), an important nuclear factor-kappaB (NF-κB) subdomain, was an effective therapeutic in atopic dermatitis and RA model animals. In this study, to develop an intra-articular injectable gel formulation against RA, we prepared a hydrogel that contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…The siRelA suppresses RelA, which is closely associated with allergy induction. 32) We also confirmed the therapeutic efficacy of siRelA in model mice with immuno-disorders using rheumatoid arthritis and AD models. 9,10,12,28,33,34) In this study, we developed an siRNA-encapsulated DOPE/ CHEMS flexible liposome with AT1002 as an effective dermally applied siRNA delivery and RNAi therapeutic system, and determined the intracellular siRNA uptake ability and cytotoxicity in macrophages of siRNA-encapsulated flexible liposomes.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The siRelA suppresses RelA, which is closely associated with allergy induction. 32) We also confirmed the therapeutic efficacy of siRelA in model mice with immuno-disorders using rheumatoid arthritis and AD models. 9,10,12,28,33,34) In this study, we developed an siRNA-encapsulated DOPE/ CHEMS flexible liposome with AT1002 as an effective dermally applied siRNA delivery and RNAi therapeutic system, and determined the intracellular siRNA uptake ability and cytotoxicity in macrophages of siRNA-encapsulated flexible liposomes.…”
Section: Introductionsupporting
confidence: 65%
“…NF-κB is overproduced in immunocompetent dendritic cells and macrophages, and regulates the expression of various inflammation-related molecules, including the inflammatory cytokines interleukin (IL)-6 and tumor necrosis factor (TNF)-α. [29][30][31] RelA (p65) is one of the two subunits of NF-κB along with p50, and is closely associated with NF-κB transcriptional activation. The siRelA suppresses RelA, which is closely associated with allergy induction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not only antibody drugs that have become mainstream for severe patients, but also antisense oligonucleotides and nucleic acid drugs such as siRNA, miRNA, and aptamer that utilize RNA interference are groundbreaking agents for inflammatory diseases as a novel drug modality [32,43,44]. There are some reports that nanoparticles such as liposomes, polymeric micelles, dendrimers, exosomes, which were loaded these modalities have been intravenously administered, and these improve therapeutic efficacy and attenuate side effects by enhancing active or passive target tissue accumulation [18,[27][28][29][30]37]. However, few studies have comprehensively analyzed what kind of physical property of nanomedicine in the treatment of inflammatory disease by intravenous administration contributes to the accumulation of inflammatory disease and the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that intravenous administration of the block-polymer micelle MPEG-PCL-CH2R4H2C and the cytoplasm-sensitive peptide STR-CH2R4H2C had strong therapeutic efficacy against inflammatory diseases such as RA and atopic dermatitis, and cancer [26][27][28][29][30][31][32][33][34][35][36][37]. These molecules were designed in our laboratory as novel drug carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with chemotherapeutic agents has several disadvantages such as poor distribution to the target tumor sites and several toxic side effects, resulting in the nonspecific distribution to healthy normal tissues. Meanwhile, intratumoral injection of chemotherapeutic agents can achieve a high local concentration of the chemotherapeutic agents at the target tumor site with no or minimal distribution to healthy normal tissues [56][57][58]. The electrostatically interactive in situ-forming hydrogel formulation with chemotherapeutic agents is expected to be easily injected through a syringe needle.…”
Section: Other Electrostatically Interactive In Situforming Hydrogelsmentioning
confidence: 99%